Accounting Challenges for Sustainability and Innovations - Marzena Remlein (ed.) (Poznań University of Economics and Business, 2021)
The aim of this e-book is to present the most important aspects related to sustainability, corporate social responsibility and innovation from an accounting perspective. The book contains parts that deal with accounting aspects of sustainability and innovations. The book consists of ten chapters devoted to relevant and topical issues of sustainability and innovations. Chapter 1 Sustainability and Corporate Social Responsibility in accounting is an introduction to further considerations and deals with the essence of sustainable development, corporate social responsibility and their recognition in accounting. Chapter 2 Social responsibility reporting standards presents the most important reporting guidance such as GRI, OECD, United Nations Global Compact, International Organization for Standardization. Chapter 3 Narrative reporting focuses on descriptions and explanations in accounting reports. The chapter presents the links between accounting and language, the development of accounting narratives and the factors determining the use of narratives. Chapter 4 Integrated reporting discusses the motivations, objectives and the process of preparing an integrated report. Integrated reporting can prove to be an effective tool for businesses looking to shift their reporting focus from annual financial performance to long-term shareholder value creation. Chapter 5 Non-financial reporting in selected European countries presents the experience of Croatia, the Czech Republic and Poland in the field of preparing non-financial reports. A significant contribution to promoting the importance of sustainability reporting was made by the Non-Financial Reporting Directive (2014/95/EU). Chapter 6 Socially responsible investments discusses the essence of socially responsible investing and socially responsible investment. Socially responsible investing (SRI) is a decision making process concerning the allocation of free financial resources, where the investor aims at maximization of profit and minimization of risk on one part and includes the socio-ethical and environmental-ecological considerations on the other. Chapter 7 External costs – accounting perspective describes costs connected with using goods such as air, soil, water, silence or the aesthetics of the surroundings. One of the biggest problems for accounting in the future will be measuring the volume of using these goods or measuring the size of reduction in the quality of public goods suffered and assigning the decrease to particular companies. Chapter 8 Derivatives in accounting is devoted to financial instruments and presents two different approaches to accounting of derivatives: general model and hedge accounting. Derivatives are used to protect the enterprise against financial risk related to changes in prices on the markets, changes in the exchange rate or changes in interest rates, as well as for commercial purposes. Chapter 9 Costs of research and development shows the company's activity in the field of research and development and the related costs. R&D constitute an increasingly important element of the functioning of enterprises. Chapter 10 Cryptoassets – nature, valuation and disclosures in accounting focuses on cryptocurrencies (e.g. Bitcoin, Ethereum etc.) and digital tokens which are specific rights or values representatives. As a result of the transformation on the financial market, we are currently dealing with cryptoassets, which are a creation of blockchain technologies and the changing habits of the digital society. One of areas that there are a lot of doubts regarding these new technological solutions is accounting.